Prehospital management of acute coronary syndromes - Śpiewak, Mateusz (Przewodnik Lekarza/Guide for GPs, 2007)
Acute coronary syndrome is a life-threatening condition, and because of that it requires prompt introduction of adequate diagnostic and therapeutic strategies. Pre-hospital management should include early diagnosis, life functions support and application of specific treatment, which should be initiated already in the patient’s home. Patients without contraindications should receive aspirin and clopidogrel as soon as possible.